Quantum evolution as a usual mechanical motion of peculiar continua - Alexey Yur'evich Samarin (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2020)
Quantum particles are considered as continuous media having peculiar properties. These properties are formulated so that all main quantum mechanics postulates can be strictly derived from them. A deterministic description of the process of position measurement is presented. The mechanism of occurrence of randomness in the measurement process is shown and the Born rule is derived. A realistic interpretation of the wave function as a component of a peculiar variable force acting on the apparatus is introduced, and the wave equation is derived from the continuity equation of the peculiar continuum. The deterministic view on the phenomena of the microcosm allows us to eliminate the limitations caused by the uncertainty principle and to describe dynamically those processes that cannot be considered using conventional quantum mechanics.